Academic Stress as a Determinant of Academic Achievement - Kar , Sasmita (Nurture, 2017)
This paper investigates the effect of academic stress on the academic achievement of senior secondary students. The Bisht Battery of Stress was chosen to collect primary data about the stress level of students studying in class XI. Academic achievement was measured by collecting data of the average marks secured by students in different examinations in an academic year. Pearson’s coefficient of correlation was applied to find out the relationship between different variables. The data revealed that there is a significant negative correlation between academic stress and academic achievement. This indicates that more the academic stress of students, the less their academic achievement.